2018
DOI: 10.1111/inm.12497
|View full text |Cite
|
Sign up to set email alerts
|

‘In some ways it all helps but in some ways it doesn't’: The complexities of service users’ experiences of inpatient mental health care in Australia

Abstract: Recovery-oriented mental health care requires active involvement of service users in the evaluation of care. While experience of care surveys is routinely given out upon discharge, capturing the depth and detail of service users' experiences in such a way to meaningfully improve services may require more in-depth and targeted approaches. This study aimed to gather voluntary and involuntary service users' experiences of care during hospitalization in two acute adult mental health inpatient units, through the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(37 citation statements)
references
References 42 publications
(56 reference statements)
2
34
0
Order By: Relevance
“…Women's responses in this study showed that the inpatient unit can be ambiguous, both an unsafe and a safe space, potentially both therapeutic and traumatizing. This finding supports reported outcomes of previous studies of inpatient milieux nationally and internationally (Isobel 2019; Muir‐Cochrane et al . 2012).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Women's responses in this study showed that the inpatient unit can be ambiguous, both an unsafe and a safe space, potentially both therapeutic and traumatizing. This finding supports reported outcomes of previous studies of inpatient milieux nationally and internationally (Isobel 2019; Muir‐Cochrane et al . 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Women's responses in this study showed that the inpatient unit can be ambiguous, both an unsafe and a safe space, potentially both therapeutic and traumatizing. This finding supports reported outcomes of previous studies of inpatient milieux nationally and internationally (Isobel 2019;Muir-Cochrane et al 2012). It is a space permeable to social and cultural influences on both clinicians and service users, its possibilities mediated by unit philosophies and practices and the persona of individual clinicians (Kanerva et al 2013).…”
Section: Building a Model For Transcultural Encounter And Recoverysupporting
confidence: 88%
See 2 more Smart Citations
“…As a result, admission to an acute unit is often oriented towards risks to physical safety such as suicide, self‐harm, substance misuse or aggression (Berzins, Baker, Brown, & Lawton, 2018). While many consumers describe feeling physically safe in acute units, others describe their emotional and psychological safety as being compromised in this setting (Isobel, 2019). Indeed, limited focus is given to consumers' emotional or psychological safety needs in acute units (Stenhouse, 2013).…”
Section: Introductionmentioning
confidence: 99%